Tubulocystic renal cell carcinoma: A case report of rare tumor - Abdullah M., Al-Jubouri (2024)
Tubulocystic renal cell carcinoma (RCC) is a rare renal cancer first recognized by the WHO in 2016 as independent disease category, characterized by its typically indolent features and low rates of metastasis. We present a 35-year-old male with tubulocystic RCC diagnosed incidentally on evaluation of flank pain. Magnetic resonance imaging showed Bosniak class 4 renal cyst, although initial computed topography showed a hypodense nonenhancing lesion classified as Bosniak 1 cyst. Patient underwent robotic assisted partial nephrectomy, histopathology confirmed as tubulocystic RCC. This case highlights the importance of considering tubulocystic RCC in the differential diagnoses of renal cysts and other solid renal masses to ensure timely and effective treatment plan.